Multiculturalist curriculum policy: diversity, subaltern cultures, and African and indigenous knowledge in teachers training and teaching multicultural basic education (Research, Society and Development, 2020)
In this article, it was proposed to discuss the emergence of decolonization of the current curriculum policy of official knowledge present in teacher training and basic education to include the perspective of multiculturalist curriculum, which represents, values and recognizes the knowledge of African and indigenous matrices, as well as social subjects of subalternized cultures. The justification is due to the important pluricultural and ethnic dimension present in the school context of Brazilian basic education, and in the current scenario the curriculum documents have reproduced the knowledge of Eurocentric, macho, monocultural and monorracist hegemony. The theoretical and methodological path fits within the phenomenological method, in relation to the approach is aligned with qualitative research and engendered in phenomenological research procedures. Among the results collected, the subjects surveyed affirmed the absence in the teacher training courses of both basic education within the official curriculum policy of knowledge misaligned with the multiculturalist curriculum perspective. It is concluded that the current curriculum policy in all levels and modalities of teaching, one of the possibilities for inclusion of all social actors in the curriculum prescribed the study pointed the perspective of curriculum policy within the multiculturalist dimension.